First Case Report of Breast Implant Associated-Anaplastic Large Cell Lymphoma from India: Are We Ready? - Khanna, Soumya; Choudhary, Sunil; Mantri, Raghav; Arora, Prateek; Arya, Anupama; Bansal, Richa; Grewal, Preeti; Bhardawaj, Nishu (Indian Journal of Plastic Surgery, 2023)
Breast implant associated-anaplastic large cell lymphoma (BIA-ALCL) has become a hot topic in recent plastic surgery and oncology forum. Its cases have been on the rise since its first emergence more than two decades ago. This condition is less known and management guidelines are still evolving. BIA-ALCL was seen recently with a classical presentation in one of our patients, who underwent immediate reconstruction with a macro-textured silicone implant following breast cancer surgery. We want to add the first case report from India to the global information database. There are still unanswered questions in its management, and we wish to highlight the same to make way for further research. With the rise in aesthetic and reconstructive implant surgeries, the knowledge of BIA-ALCL must expand among oncologists, radiologists, and pathologists for early identification and treatment for better patient outcomes.
Keywords: breast implant associated-anaplastic large cell lymphoma; breast implant lymphoma; BIA-ALCL in India